The positive impact of daily well-being practices on individual veterinary professionals’ professional quality of life self-assessment scores within an emergency and specialty hospital - Alwood, Ames J.; Ferrentino, DIana A.; Olson, Sonja A.; Rodriguez, Veronyca I. (Frontiers in Veterinary Science, 2024)
Our study set out to identify the benefits for veterinary workers of structured daily well-being practices on compassion satisfaction, burnout, and secondary traumatic stress. Suggested origins of high rates of psychological stress and burnout are significant occupational concerns for veterinary workers. Many professional helpers experience an extreme state of tension and preoccupation from exposure to the suffering of those being helped. Veterinary workers are further impacted by negative associations and moral distress experienced due to limitations in the provision of quality medical care for veterinary patients. These negative experiences exist despite veterinary professionals' work being worthwhile and highly valued.A randomized controlled study was performed over six months. Volunteer participants were members of a team of veterinary workers at a 24-hour emergency and specialty hospital. Study participants were asked to incorporate daily well-being practice(s) into existing routines whereas control participants were not. Measures of well-being and the negative impacts of serving as veterinary helpers were assessed by having participants complete the Professional Quality of Life (ProQOL) selfassessment at baseline and at 1, 3 and 6 months. Composite scores for compassion satisfaction, burnout and secondary traumatic stress were calculated.Baseline ProQOL scores were similar between study participants and controls. Baseline compassion satisfaction (CS), burnout scores (BS), and secondary traumatic stress (STS) scores for those instituting well-being practices were 37.6 (+/-3.6), 26 (+/-5.3), and 26.6 (+/-5.2). Study participants had higher compassion satisfaction scores at six months with mean CS scores (n=15) of 40.1 (+/-6.8) and adjusted scores that were on average 3.0 (95% CI 0-6.1) higher than the control group (p=0.048). Significant differences in BS or STS scores were not seen. DISCUSSION: Improvements were seen in CS but not BO/STS for those caregivers who implemented well-being practices into their daily routines. Factors that likely contributed to successful implementation of well-being practices include educational resources, supportive leadership, accessibility, and consistent acknowledgement and positive rewards. Proposed supportive elements and resources for maintenance of well-being practices within a team of veterinary workers include provision of a psychologically safe community and team support (including formal or informal "buddy systems").